The Interrelationships Between the Sustainable Development Goals and Higher Education Institutions: A Systematic Literature Review - Pacheco, Ana; Costa, Paula; Simões, Jorge; Loureiro, Rúben (Journal of Education and Training, 2023)
The objective of this systematic literature review (SLR) is to analyse the interrelationships between the Sustainable Development Goals (SDGs) and Higher Education Institutions (HEIs) based on the search for papers in the Web of Science (WoS) and SCOPUS databases. It was found that these interrelationships exist and are significant. The education and skills offered by the HEIs are essential for the development and understanding of the issues that arise and that urgently need to be resolved, namely compliance with the SDGs. On the other hand, HEIs must integrate the SDGs in their internal processes and in the course syllabuses, raising awareness and training students on issues related to the SDGs. Thus, those responsible must adopt educational policy at Higher Education (HE) that raise awareness of faculty and students all over the world to contribute with their knowledge, creativity and skills to the pursuit of the SDGs.